Structural mapping of Chikotra River basin in the Deccan Volcanic Province of Maharashtra, India from ground magnetic data - Anand, S. P.; Erram, Vinit C.; Patil, J. D.; Pawar, N. J.; Gupta, Gautam; Suryavanshi, R. A. (My University, 2016)
Ground magnetic data collected over Chikotra River in the peripheral region of Deccan Volcanic Province (DVP) of Maharashtra located in Kolhapur district was analysed to throw light on the structural pattern and distribution of magnetic sources within the basin. In order to isolate the magnetic anomalies showing varying trend and amplitude, several transformation operations including wavelength filtering, and upward continuation has been carried out on the reduced to pole anomaly map. Qualitative interpretation of these products help identify the distribution of magnetic sources, viz., the Deccan basalts, dolerite intrusives and older greenstone and schist belts in the subsurface. Present study suggests that the Chikotra basin is composed of three structural units; a NE–SW unit superposed on deeper NW– SE unit with randomly distributed trap flows on the surface. One of the major outcome of the present study is the delineation of almost 900-m thick Proterozoic Kaladgi sediments below the Deccan trap flows. The NE–SW magnetic sources may probably represent intrusives into the Kaladgi sediments, while the deeper NW–SE trends are interpreted as the northward extension of the Dharwars, underneath the Deccan lava flows, that forms the basement for the deposition of Kaladgi sediments.
Keywords: Filtering; Magnetic anomalies; Proterozoic; Dharwars; Kaladgi; Deccan lavas